ANALISIS PENERAPAN SISTEM INFORMASI AKADEMIK (SIAKAD) ONLINE DI STMIK SURYA INTAN KOTABUMI - Gustina - (Jurnal Informatika, 2016)
The development of information technology is currently so rapidly, should be well managed, there so that can help an organization improve the efficiency of the processes which take  place and can also enchane the competitiveness of an organization in terms of benefits technology excellence.STMIK Student Of University Management Informatics And Computer Surya Intan Kotabumi the field of education has been utilizing information technology, especially which is related with the teaching and learning process.STMIK Student of University Management Informatics and Computer Surya Intan Kotabumi which is has implemented an academic information systems (SIAKAD) online  specifically designed to fiil the needs of comunity colleges in an effort to improve service quality, competitiveness and quality of human  resources  which ultimately produce graduates (Output) and was able to win the global competition.Keywords: Education, Information System, Quality of Gaduate